HDL cholesterol protects from liver injury in mice with intestinal specific LXRα activation. (6th November 2020) - Pierantonelli, Irene; Lioci, Gessica; Gurrado, Fabio; Giordano, Debora M.; Rychlicki, Chiara; Bocca, Claudia; Trozzi, Luciano; Novo, Erica; Panera, Nadia; De Stefanis, Cristiano; D'Oria, Valentina; Marzioni, Marco; et al.
Abstract: Background and aims: Liver X receptors (LXRs) exert anti‐inflammatory effects even though their hepatic activation is associated with hypertriglyceridemia and hepatic steatosis. Selective induction of LXRs in the gut might provide protective signal(s) in the aberrant wound healing response that induces fibrosis during chronic liver injury, without hypertriglyceridemic and steatogenic effects. Methods: Mice with intestinal constitutive LXRα activation (iVP16‐LXRα) were exposed to intraperitoneal injection of carbon tetrachloride (CCl4 ) for 8 weeks, and in vitro cell models were used to evaluate the beneficial effect of high‐density lipoproteins (HDL). Results: After CCl4 treatment, the iVP16‐LXRα phenotype showed reduced M1 macrophage infiltration, increased expression M2 macrophage markers, and lower expression of hepatic pro‐inflammatory genes. This anti‐inflammatory effect in the liver was also associated with decreased expression of hepatic oxidative stress genes and reduced expression of fibrosis markers. iVP16‐LXRα exhibited increased reverse cholesterol transport in the gut by ABCA1 expression and consequent enhancement of the levels of circulating HDL and their receptor SRB1 in the liver. No hepatic steatosis development was observed in iVP16‐LXRα. In vitro, HDL induced a shift from M1 to M2 phenotype of LPS‐stimulated Kupffer cells, decreased TNFα‐induced oxidative stress in hepatocytes and reduced NF‐kB activity in both cells. SRB1 silencing reduced TNFα gene expression in LPS‐stimulated KCs, and NOX‐1 and IL‐6 in HepG2. Conclusions: Intestinal activation of LXRα modulates hepatic response to injury by increasing circulating HDL levels and SRB1 expression in the liver, thus suggesting this circuit as potential actionable pathway for therapy.